Criminalistics Identification as Special Criminalistics Methodand its Role in Investigating Crimes - V. V. Biryukov; T. P. Biryukova (Сибирское юридическое обозрение, 2019)
The article focuses on the basics of criminalistics identification. The authors emphasize that the emergence of the method of criminalistics identification was initiated by the need to obtain reliable knowledge about the crime event and all its components. The need to recreate a picture of the past event and establish all the objects involved in it, and as a result, its correct legal assessment from the standpoint of current legislation, initiates the use of reliable methods based on the knowledge of the natural and exact sciences by the subjects of investigation. The role and place of the considered method in identification methods, as well as the impact of the achievements of scientific and technical progress on the improvement of identification technologies are shown. It is noted that this method, as a reliable tool of knowledge, along with the investigating crimes, is increasingly being used in other spheres of human activity. A special place belongs to him in the work of modern information systems.